Influência do peso dos ovos de reprodutoras pesadas com diferentes idades sobre as características dos ovos incubáveis e pintos de um dia - Santos, Isabella Lourenço dos (2014)
Aimed to evaluate the influence of weights and ages of matrices on egg quality and quality of hatched chicks and to evaluate the correlation between the evaluated parameters (egg weight, structural characteristics of the eggs, chick size, residual yolk weight pinto , intestine weight). 3 treatments previously defined by the range of egg breeding Heavy Cobb, with 32 and 55 weeks of age were used. These being: small egg (E) 53-58 grams, medium (M) 59-64 grams and large (L) above 65 grams. We evaluated the eggs: individual weight of eggs, weight of egg components (yolk, albumen and shell), shell thickness, pore count,% mineral matter, specific gravity. Was evaluated in day-old chicks: weight and length of birds, absolute weight of the yolk sac and intestine. We evaluated% crude protein gem, clear and residual yolk of birds. Eggs of different weights bands show any difference for egg weight, egg weight of components and chick weight. The yolk weight and chick weight are directly proportional to the weight of the egg. In ages tested was observed difference between the weight of the eggs, the eggs weight of components, number of pores and size of the chick No significant difference between bark thickness, Mineral Matter and Gravity noted specifies eggs. It was concluded that there is evidence that both age of matrices as the weight of hatching eggs has effect on the performance and the quality of the bird birth mainly in the first week of life the chicks.